ASPEK EKOSOSBUD DALAM PENDIDIKAN - Mawardi Lubis (Institut Agama Islam Negeri Bengkulu, 2011)
If ekososbud support to management of education program really form better, hence national standard education of the other (content standard, process, grad interest, Educational energy, facilities and basic facilities, defrayal, and assessment) will be reached better. On the contrary, if management of education program less is getting of ekososbud support, hence will give unfavourable impact to other education national standard. To develop preeminent SDM, ekososbud role very urgen, by real efforts through function and role of[is each aspect. Economic aspect, core of its business lay in effort accomplishment of prosperity live economically. Social aspect, core of its business lay in effort pemiliharaan of good relation and friendliness with humanity and also place forward silaturrahmi and ukhuwah. While cultural core of its business lay in effort respect mores, order, manner, and kindness.